"I am still a teacher": The place of the teaching career in the process of retirement adjustment. Issue 2 (4th March 2023) - Shlomo, Haim; Oplatka, Izhar
ABSTRACT: The research examined the adjustment process to retirement among teachers during the initial stages of retirement. The focus on the specific sector of teachers is drawn from a theoretical foundation which indicates a connection between the type of work and the process of adjusting to retirement. The aim of the study was to expose the characteristics of a career in pedagogy that articulate teachers' adaptation to retirement life. Based on semi-structured interviews with 30 teachers who have been retired for two to six years, it was found that the profession of teaching is reflected in the teachers' experiences of adjusting to retirement at the psychological-personality level and the operational-practical aspect. Professional identity transfers with the teachers into retirement life. Personality traits, tendencies and skills acquired and developed during 30 years of teaching usher the teacher into the life of retirement. Moreover, the retired teacher's daily activities are influenced by his/her teaching career.